2011
DOI: 10.1016/j.ccr.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Tet2 Loss Leads to Increased Hematopoietic Stem Cell Self-Renewal and Myeloid Transformation

Abstract: SUMMARY Somatic loss-of-function mutations in the ten-eleven-translocation-2 (TET2) gene occur in a significant proportion of patients with myeloid malignancies. Although there are extensive genetic data implicating TET2 mutations in myeloid transformation, the consequences of Tet2 loss in the hematopoietic compartment have not been delineated. We report here an animal model of conditional Tet2 loss in the hematopoietic compartment which leads to increased stem cell self-renewal in vivo as assessed by competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

99
1,033
5
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,178 publications
(1,193 citation statements)
references
References 41 publications
99
1,033
5
17
Order By: Relevance
“…It was reported that the loss of Tet1 or Tet2 led to hematologic cancers (37,60,61), which are associated with low levels of 5hmC in genomic DNA (62). These results suggest that the defect in vitamin C metabolism might also be involved in cancer development or exacerbate the progression of cancers having Tet mutations.…”
Section: Discussionmentioning
confidence: 94%
“…It was reported that the loss of Tet1 or Tet2 led to hematologic cancers (37,60,61), which are associated with low levels of 5hmC in genomic DNA (62). These results suggest that the defect in vitamin C metabolism might also be involved in cancer development or exacerbate the progression of cancers having Tet mutations.…”
Section: Discussionmentioning
confidence: 94%
“…To confirm that somatic gene mutations prime HSPCs for pyroptosis in MDSs, we performed comparative analyses of published gene expression profiles from human and murine SRSF2 (GSE65349) and U2AF1 mutants (GSE30195 and GSE66793) vs WT, TET2 knockout (GSE27816), and primary MDS (GSE19429) vs normal HSPCs and found uniform upregulation of pyroptosis effectors, consistent with transcriptional priming. [39][40][41][42][43] Importantly, in MDS BM specimens, BM plasma concentration of S100A9 positively correlated with NLRP3 MFI, percentage and MFI of plasma ASC specks, and the presence of SGMs and variant allele frequency (supplemental Figure 8). Furthermore, both the percentage and MFI of plasma ASC specks were significantly increased in MDS patients harboring SGMs (supplemental Figure 8D-E).…”
Section: Org Frommentioning
confidence: 99%
“…17 Mouse models have demonstrated that Tet2 deficiency endows the cell with growth advantage over wild-type cells and have suggested that the development of a full-blown malignancy depends on the occurrence of additional mutations. 8,18,19 In our previously published Tet2-deficient models, a fraction (;30%) of aging animals develops a chronic myelomonocytic leukemia-like disease, whereas another third shows the accumulation of an abnormal B-cell population characterized by a low level of B220 at the cell surface (B220 low B cells). 8 Here, we report the analyses of the B-cell differentiation and B-cell malignancy development in both constitutive and B-cell-specific (CD19-Cre) Tet2-deficient mice.…”
Section: Introductionmentioning
confidence: 99%